Dielectric Properties of 4-Cyano-4′-pentylbiphenyl (5CB): 4-[4-(S)-2-Methylbutoxybenzoyloxy]benzoic Acid (BAC) Composite - Canli, N. Yilmaz; Ozdemir, Z. Guven; Okutan, M.; Guzeller, D.; Ocak, H.; Eran, B. Bilgin (TAYLOR & FRANCIS LTD, 2015)
Dielectric relaxation dynamics properties of 5CB (4-cyano-4-pentylbiphenyl) and BAC(4-[4-(S)-2-methylbutoxybenzoyloxy]benzoic acid) have been investigated. In this respect, dielectric properties of 5CB plus (1%)BAC have been compared with 5CB. The polarizing microscopy results show that BAC and 5CB exhibit enantiotropic N* mesophase and N mesophase, respectively. The real (epsilon ') and imaginary components (epsilon '') of dielectric constant have been calculated by capacitance method. The dielectric relaxation mechanisms of liquid crystals have been analyzed by Cole-Cole plots and the Debye distribution parameters (alpha) have been calculated. It has been also determined that adding BAC to 5CB increases the voltage dependent dielectric strength.
Keywords: 4-[4-(S)-2-Methylbutoxybenzoyloxy]benzoic acid; 4-cyano-4 '-pentylbiphenyl; absorption coefficient; dielectric strength; liquid crystal; relaxation mechanism; LIQUID; ANISOTROPY; Chemistry; Crystallography; Materials Science